GREEN INNOVATION AS A SUSTAINABLE ENTREPRENEURSHIP STRATEGY: THE ROLE OF ENTREPRENEURIAL ORIENTATION AND ENVIRONMENTAL AWARENESS - Lis Yulitasari; Ajeng Qurrota ‘Ayun; Mutiara Eka Putri (Institut Bakti Nusantara, 2026)
This study aims to analyse the roles of entrepreneurial orientation and environmental awareness in fostering green innovation as a sustainable entrepreneurship strategy among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The study is motivated by increasing global pressure regarding environmental sustainability issues and the need for MSMEs to adapt to environmentally friendly business practices in order to enhance economic performance while reducing ecological impacts. A quantitative research design with an explanatory approach was employed. Data were collected through an online questionnaire distributed to MSME owners and managers via social media platforms. The sample was selected using purposive sampling, focusing on business owners or managers who had operational business experience and knowledge related to business management and environmental issues. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine both direct and mediating relationships among the variables. The findings indicate that entrepreneurial orientation has a positive and significant effect on green innovation (β = 0.48; t = 5.21; p < 0.001), while environmental awareness also exerts a positive and significant influence on green innovation (β = 0.39; t = 4.33; p < 0.001). Furthermore, environmental awareness serves as a significant mediator in the relationship between entrepreneurial orientation and green innovation (β = 0.19; t = 3.08; p < 0.01). These findings demonstrate that the combination of an innovative, proactive, and risk-taking entrepreneurial orientation with a high level of environmental awareness constitutes a key factor in shaping sustainable green innovation strategies. The study concludes that the successful development of green innovation among MSMEs is determined not only by entrepreneurial capabilities but also by the level of environmental awareness. The practical implications suggest strengthening education and training programmes aimed at enhancing environmental awareness, integrated with entrepreneurship competency development, to facilitate the effective implementation of green innovation strategies.